Formação em serviço de professores iniciantes na educação superior e suas implicações na prática pedagógica - Viana, Maria Aparecida Pereira (2013)
This research aims to verify the pedagogical changes that teachers, who took part in the continuing education program at the Federal University of Alagoas (UFAL), managed to introduce in their classrooms. It discusses the scope of that program to a group of teachers. This study tries to answer the following research question: What are the pedagogical contributions of an inservice continuing education program offered by UFAL to their faculty hired from 2007 to 2010? In order to conduct this study, it was carried out studies on higher education, on teacher education and on the cultural scene of contemporary society that make up the theoretical framework that underpins this research. Regarding the research methodology, a qualitative approach was used with interview and observation procedures in a classroom with 11 teachers, divided into 4 teachers of Exact Sciences and 7 teachers of Health Sciences. 55 students participated in this research, being each group of 5 students from a different area. Having as research guidance the process studies stemming from a historicalcultural approach, it was established thematic areas whose matrix was the triad teacher/student/knowledge in order to study the movement of the change processes and the widening of the teaching practice. Based on the analysis and reflection of their own teaching practice, the interviewed teachers wove reflections on their teaching practices aiming at a pedagogical education and with the didactic support of virtual learning environments. From this perspective of continuing education and counting with the support of an institutional program, we understand that the adoption of an effective practice can be regarded as a starting point for formative actions, following up an emphasis on both the collective dimension of this pedagogical education and the theoretical and political deepening of this practice